The Role of Posttraumatic Growth in a Randomized Controlled Trial of Cognitive–Behavioral Conjoint Therapy for PTSD. Issue 4 (19th July 2016) - Wagner, Anne C.; Torbit, Lindsey; Jenzer, Tiffany; Landy, Meredith S. H.; Pukay‐Martin, Nicole D.; Macdonald, Alexandra; Fredman, Steffany J.; Monson, Candice M.
Abstract: Posttraumatic growth (PTG) is defined as a positive psychological change that can emerge following a traumatic life event. Although documented in noninterventional studies of traumatized individuals, there are scant data on the potential for therapy to induce or improve PTG. Thus, the primary goal of this study was to examine changes in PTG in a controlled trial of cognitive–behavioral conjoint therapy for posttraumatic stress disorder versus waitlist (CBCT for PTSD; Monson & Fredman, 2012). We also examined whether pretreatment relationship satisfaction and PTSD symptomatology moderated change in PTG. There were 40 couples (75% with a female partner with PTSD) who were randomized to either immediate CBCT for PTSD or a 3‐month waitlist (WL). Compared to WL, individuals who received treatment immediately demonstrated a significant increase in PTG. There was a moderate effect size between‐group difference (Hedge's g = 0.45). There was a nonsignificant relationship with a moderate effect size (Hedge's g = 0.65) for the positive effect of pretreatment relationship satisfaction on the trajectory of PTG, but no effect of pretreatment PTSD symptoms. Results suggested that CBCT for PTSD facilitated PTG, even with a limited focus on PTG in this conjoint intervention. Future research should target PTG as a treatment goal and further examine the role of close others in facilitating development of PTG.